Advanced Sensing Technology in Structural Health Monitoring - Giulio D’Emilia; Emanuela Natale (Sensors, 2026)
Structural Health Monitoring (SHM) has become an increasingly important research area in engineering, driven by the increasing demand for safer, more reliable, and sustainable civil structures and infrastructure, as well as industrial systems [...]